The role of social norms in incentivising energy reduction in organisations - Bradley, Peter; Leach, Matthew; Fudge, Shane (Bristol, 2014)
"This study was part of a collaborative trial for an energy feedback intervention, providing detailed individual desk based energy feedback information to help individuals reduce energy in an office environment. Although the intervention was individually based, this paper explores the social context in which the intervention took place, and in particular attempted to measure changes in normative influence (descriptive and injunctive norms) around specific energy services, before and after the intervention. Results from the study identified that social norms around certain energy services changed as a result of the intervention, and the level of descriptive norms was found to have an effect on the energy efficiency of participants. Additionally interviews which were carried out during the study are insightful in helping understand how norms emerge and spread with the influence of social context and related factors. Interviews indicate strong interactions between technologies/technology policy and social context. The findings are highly relevant in the current age of fast paced technology change where businesses and governments often make decisions on what ICT technologies shall be introduced and used (such as smart metering), without fully considering the two way relationship between these technologies and social context."